1998
DOI: 10.1088/0953-2048/11/1/006
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and properties of batch-processed melt-textured YBCO

Abstract: High-temperature superconductor bulk parts are batch processed using a semi-automated processing technique based on the melt-texturation process. Levitation properties under static and dynamic load levels were analysed using a test bench with a three-dimensional force sensor unit. Measurements of levitation force give no detailed suggestions on texture, secondary domains or cracks. Therefore other measurements to control homogeneity of the bulk were performed. Texture on full-size pellets (FWHM ) was verified … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

1999
1999
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…The TSMG technique has become the preferred method for the fabrication of bulk (RE)BCO superconductors and is used routinely in the processing of single-grain cylindrical/square shape samples of up to 50 mm in diameter [11,12]. TSMG involves seeding melt growth by a higher melting point, structurally and chemically compatible seed crystal, usually of an (RE)BCO material with a higher peritectic decomposition temperature, or MgO.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The TSMG technique has become the preferred method for the fabrication of bulk (RE)BCO superconductors and is used routinely in the processing of single-grain cylindrical/square shape samples of up to 50 mm in diameter [11,12]. TSMG involves seeding melt growth by a higher melting point, structurally and chemically compatible seed crystal, usually of an (RE)BCO material with a higher peritectic decomposition temperature, or MgO.…”
Section: Introductionmentioning
confidence: 99%
“…The seed crystal initiates the nucleation and growth of the RE-123 phase in the incongruent melt, which subsequently solidifies into a single grain during controlled cooling. However, due to the intrinsic difficulties of the solidification process, the fabrication of larger size and complex shaped bulks has proved difficult [11][12][13]. The relatively slow rate of the peritectic reaction of RE-123 phase from the incongruent melt is a particular limiting factor in extending the TSMG process to larger sizes.…”
Section: Introductionmentioning
confidence: 99%
“…As we know, the levitation force of YBCO bulk samples is closely related to the domain-size and critical current density [10], so we have to increase the domain size of the YBCO sample. Now that single domain YBCO bulk superconductors can be fabricated in many labs [11][12][13][14][15][16][17][18][19][20][21], the levitation force has been exceeded, 10 N cm −2 (77 K). It is also found that the levitation force is closely related to the thickness of the sample [22,23], magnetic field distribution [24,25], grain-orientation [26][27][28], temperature and the gap between a superconductor and a magnet [29] etc.…”
Section: Introductionmentioning
confidence: 99%
“…With the development of the top-seeded melt-growth processing technique [1], high-performance bulk superconductors are commercially available in batch process, nowadays typically with a size of 20-60 mm in diameter [2][3][4][5]. For practical cryomagnetic applications, bulk samples with larger sizes, such as over 140 mm in diameter [6], are always desired, as the enlargement of the samples can enlarge the loop size of the induced supercurrent, resulting in improved flux trapping or levitation force properties.…”
Section: Introductionmentioning
confidence: 99%